2010
DOI: 10.1002/jcp.22340
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ADAMTS1 in endothelial cells is induced by shear stress and suppressed in sprouting capillaries

Abstract: ADAMTS1 inhibits capillary sprouting, and since capillary sprouts do not experience the shear stress caused by blood flow, this study undertook to clarify the relationship between shear stress and ADAMTS1. It was found that endothelial cells exposed to shear stress displayed a strong upregulation of ADAMTS1, dependent upon both the magnitude and duration of their exposure. Investigation of the underlying pathways demonstrated involvement of phospholipase C, phosphoinositide 3-kinase, and nitric oxide. Forkhead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…16 We showed that a shear stress profile taken from an atheroprone site increases TRPC6 and TRPV1 mRNA expression in endothelial cells. Although atheroprone shear stress increased TRPC6 and TRPV1 transcripts, protein levels were not significantly affected within 24 hours.…”
Section: Thilo Et Al Trp Channels In Shear Stressmentioning
confidence: 80%
See 3 more Smart Citations
“…16 We showed that a shear stress profile taken from an atheroprone site increases TRPC6 and TRPV1 mRNA expression in endothelial cells. Although atheroprone shear stress increased TRPC6 and TRPV1 transcripts, protein levels were not significantly affected within 24 hours.…”
Section: Thilo Et Al Trp Channels In Shear Stressmentioning
confidence: 80%
“…Third, static, that is, no-flow conditions, represent nonperfused vessels and occur in vivo only in sprouting capillaries and after vessel occlusion. 16,[20][21][22] Morphological changes represent a late response of endothelial cells on flow exposure. 23 The experiments performed confirmed typical morphological changes of human endothelial cells under the influence of atheroprotective shear stress 24 versus atheroprone 25 and static …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant, soluble ADAMTS1 inhibited angiogenesis in corneal pocket and chick chorioallantoic angiogenic assays (107). In rat mesentery, Hohberg et al (48) demonstrated positive immunostaining for ADAMTS1 in microvessels experiencing flow, while there was a lack of ADAMTS1 staining in unperfused sprouts. Hohberg et al also reported that ADAMTS1 expression and liberation of TSP fragments in HUVECs increased monotonically with WSS in the range of 1 to 20 dyn/cm 2 (28).…”
Section: Introductionmentioning
confidence: 99%